Исследования на Мамай-Горе в 2009 г. - Андрух, С.И.; Тощев, Г.Н. (Археологічні дослідження в Україні, 2010)
During the excavations of the Archaeological Expedition of the Zaporizzhya National University in 2009 at the Mamay-Hora 13 graves were discovered: one of the Late Bronze Age, two of the Scythian times, and others of the Middle Ages. The Scythian burials were plundered in ancient times. A find of a large pot allows the authors to refer one of these burials to the Early Scythian period.